2014
DOI: 10.1111/desc.12236
|View full text |Cite
|
Sign up to set email alerts
|

The development of route learning in Down syndrome, Williams syndrome and typical development: investigations with virtual environments

Abstract: The ability to navigate new environments has a significant impact on the daily life and independence of people with learning difficulties. The aims of this study were to investigate the development of route learning in Down syndrome (N = 50), Williams syndrome (N = 19), and typically developing children between 5 and 11 years old (N = 108); to investigate use of landmarks; and to relate cognitive functions to route-learning ability in these groups. Overall, measures of attention and long-term memory were stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 48 publications
5
78
2
1
Order By: Relevance
“…; Purser et al . ). Thus, participants were forced to rely on the information preceding the junction to make their decision, which could have hindered the WS group.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Purser et al . ). Thus, participants were forced to rely on the information preceding the junction to make their decision, which could have hindered the WS group.…”
Section: Discussionmentioning
confidence: 97%
“…Both Purser et al . () and Broadbent et al . (), who also used distant landmarks only, suggest that their WS group were using a visual recognition view‐matching strategy in which they evaluate whether the visual scene (including landmarks) had been seen before and is part of the correct route, rather than pairing a landmark with a directional decision (e.g.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…It was found that participants in both groups could learn routes, but those with ID often could not find the shortest path. Other uses of virtual environment based experiments include the work of Purser et al [6]. The authors investigated the development of route learning and the use of landmarks in DS, Williams syndrome (WS), and typically developing children between the ages of 5 and 11.…”
Section: Related Workmentioning
confidence: 99%